The Influence Of Reflexology Massage Education On Increasing The Knowledge Of Diii Midwifery Students At Batari Toja (Comprehensive Health Care, 2024)
The Effect of Reflexology Massage Education on Increasing Knowledge of DIII Midwifery Students in Batari Toja, Reflexology massage or reflexology is one of the complementary therapy methods that is increasingly popular in the world of health. In the context of midwifery, reflexology has great potential to improve the welfare of pregnant and lactating mothers. Reflexology is a therapy technique that focuses on certain points, such as the feet, hands and ears. However, there is still limited research on the effectiveness of reflexology massage education on midwifery students. In fact, midwifery students have an important role in providing information and support to pregnant and lactating mothers. Therefore, this study aims to examine the effect of reflexology massage education on increasing the knowledge of DIII Midwifery students. And also aims to analyze the effect of reflexology massage education on increasing the knowledge of DIII midwifery students in Batari Toja. This study uses a quantitative method with a quasi-experimental research type with a pretest-posttest group design. The sample used was 38 students of Dlll Midwifery Batari Toja consisting of two classes, namely class 2A consisting of 20 students and Class 2B consisting of 18 students. Students' knowledge was measured before and after being given education using a knowledge test or questionnaire. Based on the results of the Wilcoxon Signed-Ranks Test, it can be concluded that, There is a significant increase in knowledge with a value of p = 0.000 p <0.05 which means there is an increase in knowledge of Dlll Midwifery Batari Toja students. Reflexology education has proven effective in increasing the knowledge of Dlll Midwifery Batari Toja students. This Learning Method has succeeded in significantly increasing the knowledge of DIII midwifery students and can be used to improve the quality of Midwifery education. Keywords: Knowledge, Massage, Reflexiology, Students